Global Muhasebe Sürecinde Yakınsama Eğilimleri - (:unkn) unknown (My University, 2004)
Günümüzde global ekonomi koşullarında, yüksek kaliteli ve uluslararası boyutta karşılaştırabilir finansal bilgi talebi oldukça önem kazanmıştır. Son zamanlarda birçok kuruluş finansal raporların karşılaştırılabilirliğini arttırma yönünde önemli çaba harcamışlardır. 2005'de Avrupa Birliği'nde hisse senetleri borsada işlem gören işletmelerin raporlarında uluslararası standartların zorunlu tutulmuş olması bu süreci hızlandırmıştır. IFRS'ler, ortak bir finansal raporlama dili oluşturmada yakınsama sürecinin en önemli düzenlemeleridir. Bu çalışma, global muhasebe sürecinde muhasebe yakınsamasını ve IFRS'leri incelemektedir.

The globalisation of economic activity has resulted in an increased demand for high quality, internationally comparable financial information. Over the past few decades numerous organizations have been actively participating in the efforts to improve the comparability of financial reporting. The worldwide acceptance of IAS has received a significant boost now that reporting in accordance with IAS is required for public companies within the EU by 2005. This development also has increased pressure for convergence between international and US accounting standards. IFRS moves the integration process forward by establishing a common financial reporting language that can make capital markets more efficient. This study investigated the accounting convergence and IFRS's on the global accounting process.
Towards Convergence on the Global Accounting Process
Keywords: İşletme Finans; İktisat; Uluslararası İlişkiler; İşletme